The Opposition to the Great War in Wales 1914-1918 - Aled Eirug (University of Wales Press, 2018)
This study describes and analyses the opposition to the Great War in Wales and considers the literature of the history of the War and Wales. it analyses the anti-war political movement, headed by the Independent Labour Party and the left within the South Wales Miners' Federation, and on religious grounds from the Fellowship of Reconciliation and led by the grouping around the anti-war journal , Y Deyrnas (The Kingdom). It reveals for the first time the numbers of conscientious objectors in Wales, the basis on which they opposed the war, and how they responded to the Government and the military's attempts to co-opt them within the framework of the Army.